SAFETY AND HEALTH CHALLENGES ON INDIVIDUAL AND ORGANIZATION PRACTICE OF MALAYSIAN SMEs - Shazwani Mohd Salleh; Norhafizah Abdul Halim; Roziyana Jafri; Nurul Farhana Nasir (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Occupational safety and health are especially important in the new normal era due to the pandemic threat which may have implications for individuals and organizations. Moreover, accidents and injuries in the workplace can cost the organizations financially and non-financially. Although workplace safety has been widely investigated, less consideration is given to the small and medium enterprises. Regrettably, majority of workplace accidents come from SMEs. Furthermore, workplace accidents cause a lot of problems for SMEs such as loss of production time and compensation cost. In Malaysia, the incidence of workplace accidents has been rising in recent years, with the SMEs sector accounting for 80–90% of these incidents. As a result, the study’s discussion of health and safety-related issues and challenges in Malaysian SMEs is centred on how these issues may affect the SMEs’ ability to grow. Given the increased significance of occupational health and safety, a number of suggestions and solutions are made.